2004
DOI: 10.1074/jbc.m405006200
|View full text |Cite
|
Sign up to set email alerts
|

SUMO Modification of Repression Domains Modulates Function of Nuclear Receptor 5A1 (Steroidogenic Factor-1)

Abstract: Steroidogenic factor 1 (SF-1 or NR5A1), is a Ftz-F1 member of the nuclear receptor superfamily that plays essential roles in endocrine development, steroidogenesis, and gonad differentiation. We investigated modifications that control SF-1 function and found that SF-1 could be conjugated by SUMO-1 both in vitro and in vivo. Wild-type but not conjugation-deficient SF-1 was localized at the nuclear speckles together with SUMO-1. Thus, SUMO-1 conjugation could also target SF-1 into nuclear speckles. Collectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 31 publications
(34 reference statements)
8
82
1
Order By: Relevance
“…Fourth, it has been proposed that SUMO-1 conjugation targets proteins to different cellular localizations. SF-1 can be directed into nuclear speckles and sequestered from the nucleolus in the presence of SUMO-1, thus resulting in transcriptional repression (43). It is therefore important to investigate whether and how MR activity and subcellular localization are functionally linked for further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, it has been proposed that SUMO-1 conjugation targets proteins to different cellular localizations. SF-1 can be directed into nuclear speckles and sequestered from the nucleolus in the presence of SUMO-1, thus resulting in transcriptional repression (43). It is therefore important to investigate whether and how MR activity and subcellular localization are functionally linked for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable numbers of nuclear receptors, including glucocorticoid receptor (26 -30), androgen receptor (21,22,(31)(32)(33)(34)(35)(36), progesterone receptor (36,37), MR (38), estrogen receptor ␣ (39), peroxisome proliferator-activated receptor ␥ (40 -42), and SF-1 (43)(44)(45), are modified by SUMO through a series of enzyme reactions, and sumoylation of the receptors mostly resulted in repression of the receptor-dependent transcription. In this study, we focused on the protein-protein interaction between Ubc9 and MR. We describe a new function of Ubc9 as a coactivator of MR by formation of a complex with N-terminal MR and SRC-1 beyond the known SUMO E2-conjugating enzyme, although sumoylation of MR repressed the receptor-dependent transactivation.…”
mentioning
confidence: 99%
“…Although an oxysterol was reported to activate SF-1 (40), this finding could not be confirmed (41). Alternative modes of regulation for SF-1, including phosphorylation (42,43) and sumoylation (44), have been presented. A recent mouse LRH-1 (mLRH-1) structure revealed it to have a large empty pocket, but mutations made to fill this pocket did not reduce the transcriptional activity, which suggested that the activity of mLRH-1 may be ligand-independent (45).…”
mentioning
confidence: 83%
“…Phosphorylation of serine-203 is key for coactivator binding and the transactivation potential of the receptor (Hammer et al, 1999). The ability of SF1 to activate target gene expression is also regulated by SOMUylation (Chen et al, 2004;Komatsu et al, 2004;Lee et al, 2005), acetylation (Chen et al, 2005;Ishihara and Morohashi, 2005;Jacob et al, 2001), and interaction with various coregulatory proteins (Chen et al, 2005).…”
Section: Regulation Of Sf1 Activitymentioning
confidence: 99%